Flashover phenomena of polluted insulators energized by AC voltage - Salam, Md. Abdus (Faculty of Electrical Engineering, 1999)
The study of polluted insulator flashover mechanism very important for electric power transmission reliability, efficiency and sewiceability. In this paper, a new mathematical model based on Ayrton arc voltage gradient equation, which takes account of total resistance of the polluted insulator rather than the pollution resistance value has been proposed. The expression of total resistance of the insulator is also derived. The value of critical flashover voltage (CFV) obtained from the model is in good agreement with the ones obtained through experimental results.